Effects of different polishing systems on the surface roughness of esthetic composite resins - Ceren Özge Biçer; Fatma Dilşad Öz; Nuray Attar; Yonca Korkmaz (Gazi University, 2017)
Objective: The aim of this in vitro study was to evaluate the surface roughness of esthetic composite resins finished and polished with 2 different one-step polishing systems and a conventional multi-step disc system. Materials and Method: The evaluated composite resins were: Filtek Ultimate (3M ESPE), Amaris (Voco) and Esthet-X HD (Dentsply). A total of 120 specimens were fabricated in a plexiglass mold covered with a mylar strip. After polymerization, ten specimens per group received no polishing treatment and served as the control group. For each composite resin group (n=30), the specimens were randomly divided into three polishing systems: Enhance (one-step; Dentsply), OptraPol (one-step; Ivoclar Vivadent) and Sof-Lex (multiple-steps; 3M ESPE). All polishing systems were applied according to the manufacturers' instructions. The surface roughness values were determined using a profilometer. Data were analyzed using One-way ANOVA and post hoc Tukey tests (α=0.05). Results: The smoothest surfaces were achieved under mylar strips in all composite resin groups (p=0.00) except for Esthet-X HD. For Esthet-X HD, OptraPol exhibited similar roughness values with the control group. For Filtek Ultimate, Sof-Lex exhibited statistically greater surface roughness values compared to other polishing systems (p=0.00). However, in Amaris groups there were no statistically significant differences between the polishing systems (p=0.998). Conclusion: Surface roughness values differ between composite resin materials. For polishing esthetic composite resins, one-step polishing systems may exhibit comparable results with multi-step system.